GBP2 as a potential prognostic predictor with immune-related characteristics in glioma - Li, Ren; Wang, Yuan-Yuan; Wang, Shu-Le; Li, Xue-Peng; Chen, Yang; Li, Zi-Ao; He, Jian-Hang; Zhou, Zi-Han; Li, Jia-Yu; Guo, Xiao-Long; Wang, Xiao-Gang; Wu, Yong-Qiang; et al. (Frontiers in Genetics, 2022)
Guanylate binding protein 2 (GBP2) is a member of the guanine binding protein family, and its relationship with prognostic outcomes and tumor immune microenvironments in glioma remains elusive. We found GBP2 were increased in glioma tissues at both mRNA and protein levels. Kaplan-Meier curves revealed that high GBP2 expression was linked with worse survival of glioma patients, and multivariate Cox regression analysis indicated that high GBP2 expression was an independent prognostic factor for glioma. Combined analysis in immune database revealed that the expression of GBP2 was significantly related to the level of immune infiltration and immunomodulators. Single-cell analysis illustrated the high expression of GBP2 in malignant glioma cells showed the high antigen presentation capability, which were confirmed by real-time polymerase chain reaction (qRT-PCR) data. Additionally, the hsa-mir-26b-5p and hsa-mir-335-5p were predicted as GBP2 regulators and were validated in U87 and U251 cells. Our results first decipher immune-related characteristics and noncoding regulators of GBP2 in glioma, which may provide insights into associated immunotherapies and prognostic predictor.